Framework Action Plan for Foodgrain Production Report of the Task Force March 1988 - Planning Commission (Planning Commission, 1988)
Based on an analysis of soil conditions, water availability through surface and ground water schemes, existing ICAR technological packages available at the regional level (each region consisting of a cluster of districts), existing levels of development and rates of growth of the agricultural sector generally over the past two decades, and of the foodgrain sector particularly in the past few years, 169districls were identified in 14 States for the Action Plan. In these districts, 108 have potential for paddy, 68 for wheat, 27 for maize, 20 for arhar and 28 for gram.
Planning Commission Government of India
Planning Commission Government of India